Prediction of protein venom epitope (kistomin) from Calloselasma rhodostoma using immunoinformatics to design vaccine based on epitope - Zyana Fithri Nur Faizah; Nia Kurniawan; Fatchiyah Fatchiyah (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2021)
Vaccines based on epitope are alternative treatments for snakebite aside from anti-venom immunoglobulin, which is specific and not cross-reaction. However, the potential kistomin epitope has not been known. This study identified the region of T cells epitope and evaluated their immunogenicity to induce an immune response by in-silico. Sequences of kistomin were collected from Swiss-Prot with ID P0CB14. The physico-chemical and conserved domain of kistomin were predicted by using ProtParam and the NCBI database. The T cell epitope was predicted by using the Artificial Neural Network (ANN) method on the IEDB website. Epitopes with MHC-IC50 values >250 nM were further analyzed for conservation and immunogenicity on the IEDB website as well. After that, the candidate 9-mer epitope was interacted by simulated docking with four Major Histocompatibility Complex (MHC) molecules (5ENW, 6VB0, 3PGD, 6DIG). The conserved 9-mer epitope candidates with high immunogenicity and having similarities with the 15-mer epitope candidates are 4-VLLVTICLA-12 and 27-NVNDYEVVY-35. The 4-VLLVTICLA-12 candidate epitope interacted at β-sheet structure of four MHC. In contrast, The 27-NVNDYEVVY-35 candidate epitope interacted at α-helix and β-sheet structures of HLA-B*15:02 MHC. This study suggested 27-NVNDYEVVY-35 is potentially used as vaccine from envenomation Calloselasma rhodhostoma. In future studies, other alelles can be used to predict epitope from metalloproteinase domain in kistomin.